GE_GERICHTE DCSO/453/2012 vom 22. November 2012 - GE Cour de justice (2012)
Résumé: Recours interjeté au TF le 4 décembre 2012 par la débitrice, rejeté par arrêt du 10 janvier 2013 (5A_896/2012/ZEH/bnm).